2014
DOI: 10.1371/journal.pone.0096493
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 17 Organophosphate Pesticide Residues in Mango by Modified QuEChERS Extraction Method Using GC-NPD/GC-MS and Hazard Index Estimation in Lucknow, India

Abstract: A total of 162 samples of different varieties of mango: Deshehari, Langra, Safeda in three growing stages (Pre-mature, Unripe and Ripe) were collected from Lucknow, India, and analyzed for the presence of seventeen organophosphate pesticide residues. The QuEChERS (Quick, Easy, Cheap, Effective, Rugged and Safe) method of extraction coupled with gas chromatography was validated for pesticides and qualitatively confirmed by gas chromatography- mass spectrometry. The method was validated with different concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 20 publications
1
12
1
Order By: Relevance
“…Alegantina et al, (2005) described a negative result or absence of the organophosphate residue, such as diazinon, chlorpyrifos, metidation, phention, phenitroin, phenthoate, profenofos, protiofos, triazophos, methamidophos and dimethoate, within tomatoes and lettuces from various traditional and supermarkets in Jakarta. Srivastava et al, (2014) showed the presence of low level organophosphate residue, Malathion and chlorpyrifos, in the mango examined in Lucknow, India. Putu et al, (2016) analyzed the presence of benzophenone, 2,6-diisopropylnaphthalene, and ftalat acid, instead of organophosphate, in the strawberry samples from Candikuning Market, Bedugul, Bali.…”
Section: Resultsmentioning
confidence: 97%
“…Alegantina et al, (2005) described a negative result or absence of the organophosphate residue, such as diazinon, chlorpyrifos, metidation, phention, phenitroin, phenthoate, profenofos, protiofos, triazophos, methamidophos and dimethoate, within tomatoes and lettuces from various traditional and supermarkets in Jakarta. Srivastava et al, (2014) showed the presence of low level organophosphate residue, Malathion and chlorpyrifos, in the mango examined in Lucknow, India. Putu et al, (2016) analyzed the presence of benzophenone, 2,6-diisopropylnaphthalene, and ftalat acid, instead of organophosphate, in the strawberry samples from Candikuning Market, Bedugul, Bali.…”
Section: Resultsmentioning
confidence: 97%
“…This practise is misleading with regards estimation of the actual risk and should be discouraged. An example of this case is when chemicals are grouped on the basis of their assumed toxicity as in the case for organophosphorus (OP) pesticides which are known to cause neurological effects [19]. However, as we demonstrate in one of our case studies [27], the ADIs may be based on different critical effects and different than the generally assumed toxicity, again leading to an unrealistic risk assessment.…”
Section: Introduction and Problem Formulationmentioning
confidence: 99%
“…HQ and HI methodologies for risk characterisation, whilst considering a single route or a single source of exposure, have since been implemented in a number of studies. This is the case with many dietary studies where the estimation of risk has been associated with the concentrations of chemicals in a specific food item [[17], [18], [19], [20], [21], [22], [23], [24], [25], [26]]. The lack of availability of data and/or the capacity to estimate actual aggregated exposure has likely driven the calculation of a HQ based on exposure to one food item only.…”
Section: Introduction and Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesticides residues have been found in food materials from both developed and developing countries [4,[9][10][11], but a higher prevalence of residues exceeding the MRLs are observed in food products from developing countries. These foods exceeding the tolerance of pesticide residues in foods are consumed by the general public, pausing public health concern due to increased risk of detrimental effects of pesticide exposure.…”
Section: Introductionmentioning
confidence: 99%